Synthesis and Docking Studies of Alkylene-linked Dimers of (−)-Huperzine A - Jin, Guangyi; Luo, Xiaomin; He, Xuchang; Jiang, Hualiang; Zhang, Haiyan; Bai, Donglu (Arzneimittelforschung, 2003)
(−)-Huperzine A (5, HupA), an alkaloid isolated from the herb Huperzia serrata, is a potent, selective and reversible acetylcholinesterase (AchE) inhibitor. Based on the hypothesis with respect to two binding sites in the active gorge of AChE and the good example of bis-tacrine, it was predicted from the docking studies of alkylene-linked dimers of HupA that dimers 6 (n = 5, 7, 9) might have good AChE inhibitory activity. Therefore, six dimers with 7−12 methylene units as tethers were thus prepared. It was found that these dimers were less potent than HupA in inhibition of AChE. The difference of the inhibitory potency between these dimers is coincident with the results of the docking studies.
Keywords: Acetylcholinesterase, inhibition; (−)-Huperzine A, alkylenelinked dimers, docking studies